Modeling How the Leader Power Affecting Performances of the Smallholder Beef Farming - Novie Andri Setianto; Nunung Noor Hidayat; Pambudi Yuwono (Buletin Peternakan, 2018)
This study aimed to explore how the leader power is affecting the performance of beef farmer group. The research was undertaken in two farmers group in Kabupaten Banjarnegara, Central Java Province involving 35 farmers and two beef traders. Systems thinking the approach was chosen about its capability to capture the complexity of the beef farming systems. A combination of semi-structured interviews, in-depth interviews, and workshop have been conducted to finalize this study. The discussion were focused on three aspects; (1) daily activities; (2) resources used and affected by those activities; and (3) pressures that are directly affected the resources and activities. The result was presented in a Causal Loop Diagram (CLD) which generated using Vensim® software. The CLD showed that leader power affects the group performance in two reinforcing loops. Firstly, leader power positively linked to the decision for allocating profit to group reinvestment. Secondly, for allocating proportion for breeding. Farmer’s actual income become the leverage of the power dimension. Income will enforce the power thus makes the loop virtuous, whereas a loss will reduce power and makes the power loop vicious.